Asymptomatic Extradural Hematoma-Our Observation In DMCH - Das, Sukriti; Ghosh, Dipankar; Sarkar, Asit Chandra; Khan, Mohammed Shamsul Islam (Bangladesh Journal of Neurosurgery, 2020)
Background: Surgical management of extradural hematoma is evacuation of extradural hematoma until otherwise. But, a number of authors have suggested that small epidural hematoma may be managed conservatively with normal outcome in selected cases. The goal of this study was to define the clinical and radiological parameters that may help in the management of the patient with small epidural hematoma where the hematoma was asymptomatic. Objective: This study was conducted to find out the factors influencing the decision making in the management of asymptomatic extradural hematoma though they have no evidence of raised intracranial pressure or any focal neurological deficit. Methods: Three hundred patients were evaluated clinically and by CT scan of head to see of hematoma, location of hematoma, midline shifting and overlying skull fractures etc. Results: All 300 patients were diagnosed within 72 hours of trauma and were tired to be managed expectantly but was not possible sometimes. All these patients were analyzed on the basis of tome since trauma, GCS score, overlying skull fracture traversing any artery, vein or any venous sinuses. Among 300 patients 225 (75%) patients underwent CT scan of head within 24 hours of trauma and 185 (61.67 %) patients had overlying skull fracture. 51 (17%) deteriorated later on and 31 (10.33%) patients among them required surgical evacuation of hematoma. Conclusion: It can be concluded that patients with small epidural hematoma with a fracture overlying major vessels or major sinuses, diagnosed within 24 hours of trauma are at risk of subsequent deterioration and may require surgical evacuation. Bang. J Neurosurgery 2020; 10(1): 20-26